Alkali activation of recovered fuel–biofuel fly ash from fluidised-bed combustion: Stabilisation/solidification of heavy metals. (September 2015) - Yliniemi, Juho; Pesonen, Janne; Tiainen, Minna; Illikainen, Mirja
Graphical abstract: Highlights: Recovered fuel–biofuel fly ash from FBB used as alkali-activation precursor. High-shear granulation applied in the sample preparation. Ba, Pb and Zn immobilised. Sequential leaching procedure proved that bioavailable amount of heavy metals reduced. Abstract: Recovered fuel–biofuel fly ash from a fluidized bed boiler was alkali-activated and granulated with a sodium-silicate solution in order to immobilise the heavy metals it contains. The effect of blast-furnace slag and metakaolin as co-binders were studied. Leaching standard EN 12457-3 was applied to evaluate the immobilisation potential. The results showed that Ba, Pb and Zn were effectively immobilised. However, there was increased leaching after alkali activation for As, Cu, Mo, Sb and V. The co-binders had minimal or even negative effect on the immobilisation. One exception was found for Cr, in which the slag decreased leaching, and one was found for Cu, in which the slag increased leaching. A sequential leaching procedure was utilized to gain a deeper understanding of the immobilisation mechanism. By using a sequential leaching procedure it is possible fractionate elements into watersoluble, acid-soluble, easily-reduced and oxidisable fractions, yielding a total 'bioavailable' amount that is potentially hazardous for the environment. It was found that the total bioavailable amount was lower following alkali activation for all heavy metals, although the water-soluble fraction was higher for some metals. Evidence from leaching tests suggests the immobilisation mechanism was chemical retention, or trapping inside the alkali activation reaction products, rather than physical retention, adsorption or precipitation as hydroxides.